미량오염물질 제거능 향상을 위한 생물활성탄 공정의 강화 - 손희종(Heejong Son); 정은영(Eun-Young Jung); 염훈식(Hoonsik Yoom); 최상기(Sangki Choi); 박홍기(Hong-Ki Park) (Daehan hwan'gyeong gonghag hoeji, 2023)
목적 : 본 연구에서는 생물막 특성이 강화된 BAC 공정에서의 미량오염물질의 제거효율을 일반 BAC 공정과 비교·평가하여, 정수장의 BAC 공정에서 미량오염물질의 제거효율을 상승시킬 수 있는 방안을 제시하고자 하였다. 방법 : 대상 미량오염물질로는 dibromo-methylparaben (Br2-MP)를 선정하였다. 회분식 실험과 실험실 규모 컬럼 실험을 수행하여 일반 BAC 공정과 인(P) 및 과산화수소(H2O2)를 첨가하여 생물막 특성을 강화한 BAC에서 Br2-MP의 제거 효율을 평가하였다. 회분식 및 실험실 규모의 컬럼 실험 결과를 사용하여 생분해 동역학을 평가하였다. 결과 및 토의 : 동일한 생체량 조건(2.0±0.2×107 cells)에서 Br2-MP의 제거효율을 비교한 회분식 실험에서 생물학적 활성도가 높게 나타난 강화 BAC 공정의 생물분해 속도상수(kbio)는 일반 BAC 공정보다 1.2배 높았다(강화 BAC: 3.4±0.3 mg·C/g·hr, 일반 BAC: 2.9±0.4 mg·C/g·hr). 동일한 습중량(1 g) 조건으로 Br2-MP의 제거효율을 비교한 회분식 실험에서, 생체량 함량이 높은 강화 BAC 공정의 생물분해 속도상수(kbio)는 일반 BAC 공정보다 1.9배 더 높았다(강화 BAC: 3.5±0.4 µg·ATP/g·GAC, 일반 BAC: 2.3±0.2 µg·ATP/g·GAC). 회분식 실험을 통해 강화 BAC 공정은 부착된 박테리아의 생체량과 활성이 증가하여 Br2-MP 제거에 더 효율적이었다. 다양한 수온(5, 25℃)과 공탑 체류시간(EBCT: 5-40분) 조건에서 실험실 규모의 컬럼 실험을 진행한 결과, 전체 운전 기간 동안 일반 BAC 공정에 비해 강화 BAC 공정에서 Br2-MP의 제거효율이 더 높은 것으로 나타났다. 특히, 저온(5℃)과 짧은 EBCT(5분)에서 강화 BAC 공정과 일반 BAC 공정의 Br2-MP 제거효율은 큰 차이를 나타내었다. 5℃와 25℃에서 일반 BAC 공정의kbio는 각각 0.0229 min-1, 0.0612 min-1, 강화 BAC 공정의 kbio는 각각 0.0470 min-1, 0.1421 min-1로 강화 BAC 공정이 일반 BAC 공정에 비해 2배 이상 빠른 Br2-MP 생분해능을 나타내었으며, 이러한 결과는 회분식 실험결과와도 유사하였다. 또한, 하절기 잦은 EBCT 변경에 대한 영향을 시뮬레이션한 실험에서 강화 BAC 공정은 일반 BAC 공정에 비해 상대적으로 안정적인 Br2-MP 제거효율을 유지하였다. 결론 : 강화된 BAC 공정은 일반 BAC 공정에 비해 우수한 미량오염물질 생물분해능을 나타내었다. 다만 경제성(인산염과 과산화수소 비용 등)과 수질을 고려할 때 하절기와 같이 EBCT가 단축되거나 수온이 낮아지는 동절기에 한하여 간헐적으로 강화 BAC 공정을 운영하는 것도 효율적인 대안으로 평가되었다. Objectives : In this study, the removal efficiency of micropollutants in the biological activated carbon (BAC) process was investigated, and a method for improving the removal efficiency of micropollutants in the BAC process of water treatment plants was proposed.Methods : Dibromo-methylparaben (Br2-MP) was selected as the target micropollutant. Batch and lab-scale column experiments were conducted to evaluate the removal efficiencies of Br2-MP in the conventional BAC process and the BAC with enhanced biofilm properties by the addition of phosphorus (P) and hydrogen peroxide (H2O2). Biodegradation kinetics were evaluated using results from batch and lab scale column experiments.Results and Discussion : As a result of comparing the removal efficiency of Br2-MP in a batch experiment with the same biomass concentrations (2.0±0.2×107 cells), the biodegradation rate constant (kbio) of the enhanced BAC process was found to be 1.2 times higher than that of the conventional BAC process due to its higher biological activity (enhanced BAC: 3.4±0.3 mg·C/g·hr, conventional BAC: 2.9±0.4 mg·C/g·hr). Comparison of removal efficiencies of Br2-MP in batch experiments with the same wet weight of BAC (1 g) showed that the biodegradation rate constant (kbio) of the enhanced BAC process was 1.9 times higher than that of conventional BAC process due to higher biomass (enhanced BAC: 3.5±0.4 µg·ATP/g·GAC, conventional BAC: 2.3±0.2 µg·ATP/g·GAC). Through the batch experiments, the enhanced BAC process was efficient in removing Br2-MP via increasing both biomass concentrations and activity of attached microorganisms. Lab-scale column experiments conducted under different water temperatures (5 and 25℃) and empty bed contact time (EBCT: 5-40 min) conditions showed higher removal efficiency of Br2-MP in the enhanced BAC process than the conventional BAC process throughout the entire period of operation. In particular, the removal efficiency of Br2-MP between the enhanced and conventional BAC processes showed significant differences at low temperature (5℃) and short EBCT (5 min). At 5℃ and 25℃, the kbio of the conventional BAC process was 0.0229 min-1 and 0.0612 min-1, respectively, and the kbio of the enhanced BAC process was 0.0470 min-1 and 0.1421 min-1, respectively, These results showed that the enhanced BAC process had two times higher biodegradability of Br2-MP than the conventional BAC process. These results showed a similar trend to the results from the batch experiment. In an experiments simulating the impact of frequent EBCT changes during summer, the enhanced BAC process maintained a relatively stable removal efficiency of Br2-MP compared to the conventional BAC process.Conclusion : The enhanced BAC process showed superior biodegradation of micropollutant compared to the conventional BAC process. Considering economic costs (e.g., costs of adding phosphate and hydrogen peroxide) and water quality, it appears to be an efficient alternative to operate the enhanced BAC process intermittently, limited to cases where EBCT is shortened, such as summer, or when water temperature is low, such as in winter. KCI Citation Count: 0